Multicomponent Pharmaceutical Solids - Choquesillo-Lazarte, Duane; Dominguez-Martin, Alicia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Multicomponent pharmaceutical materials are solids in which at least one component is an active pharmaceutical ingredient (API). This kind of pharmaceutical solid has attracted interest in the past decade as a promising alternative to the laborious and expensive process of traditional pipeline drug development. The application of crystal engineering techniques into the design of pharmaceutical salts, co-crystals, and other multicomponent materials, in addition to the achievement of more environmentally friendly synthetic approaches, has succeeded in modulating the physicochemical, mechanical, and pharmacokinetic properties of drugs, thereby working toward the enhancement of their clinical performance. This Special Issue welcomed original research articles and reviews devoted to all aspects related to the field of multicomponent pharmaceutical solids. Our interests include the fundamentals of applied research, using theoretical and experimental approaches, the development of synthetic methods, the screening of multicomponent materials, structure-activity rationale, the salt-co-crystal continuum identification, the enhancement in physicochemical/mechanical/pharmacokinetic performance, as well as the functionality and applications of multicomponent pharmaceuticals solids.